A planted forest in the mountain steppe of Tabriz, Iran: Visitor’s perceptions of Eynali Urban Woodland Park - Sabouri, Ramin; Breuste, Jürgen; Rahimi, Akbar (Frontiers in Forests and Global Change, 2023)
Eynali Urban Woodland Park (EWP) is a large mountain park in Tabriz, Iran, and is the largest urban woodland park in Iran. It was developed to increase the urban green space in the growing city of Tabriz for recreation, climate improvement, biodiversity, and ecological connection between the city and its natural surroundings. The planted hilly woodland is located in a natural mountain steppe in a semi-arid region and needs intensive management, including irrigation. By questioning 277 randomly selected park visitors' frequency of visits, activities, accessibility, preferences, and especially nature preferences were analyzed using visualization of different nature types by photographs. The management targets were compared to visitors’ perceptions, preferences, and acceptances. The results show, that visitors prefer natural surroundings instead of artificial landscape design. Expectations of visitors for specific natural design attractions are lower than the actual status offers, and higher for social security, quality of infrastructure, accessibility, and utilization. Especially important are security by monitoring and guarding, enhancing picnic sites, improving the lighting system for evening visits, continuing forestry, public transport, and providing natural risk protection. Most visitors prefer nature-near vegetation, dry grassland with shrubs partly planted with trees and bushes, followed by planted forest. The planted forest is not the preferred preference. Vistors’ mental nature imagination matches quite well with the nature experience they have from the surrounding mountain steppe with forest patches. Conclusions: The use of the visitors’ expectations can improve the park landscape management can reduce the management costs.